Clinical and radiological outcomes of acute Rookwood type IIIB acromioclavicular joint dislocation: Mini-open tightrope technique versus hook plate. (April 2023) - Yu, Pei; Zhang, Yin; Ye, Tingjun; Liu, Jingfeng; Zhuang, Chengyu; Wang, Lei
Highlights: "Mini-open tightrope fixation" was a reliable and effective method for type IIIB AC joint dislocation. The effect of "mini open tightrope fixation" is better than that of classical hook plate fixation. The mini-open tightrope has better function and relieves pain in the early postoperative period compared to hook plate. Abstract: Objective: Treatment of acute Rookwood type III AC joint dislocation is still controversially discussed. ISAKOS suggested to subdivide type III AC joint injuries into type IIIA (stable) and type IIIB (unstable). The aim of this study was to compare clinical and radiographic outcomes between hook plate fixation and mini-open tightrope for the treatment of acute Rookwood type IIIB acromioclavicular joint dislocation. Methods: We conducted a retrospective clinical study of 112 patients with acute Rookwood type IIIB acromioclavicular joint dislocation who were treated surgically using either mini-open TightRope or hook plate from 2013 to 2019. All patients were followed up for 12 months. Clinical outcomes were evaluated using Visual Analogue Scale (VAS) and the Constant-Murley Score (CMS). Radiological results were assessed with the coracoclavicular distance (CCD), the change in clavicular elevation (ΔCE) and horizontal translation. Results: The length of incision was significantly shorter in the mini-open TightRope group than that in hook plate group (6.62±0.60 vs. 2.58±0.43 p <0.001). Duration of surgery was significantly shorter in the mini-open TightRope group than that in hook plate group (30.12±6.65 vs. 53.33±12.03; p < 0.001). Total blood loss volume was significantly less in the mini-open TightRope group than in the hook plate group. (23.85±7.88 vs. 70.67±24.62, p < 0.001). VAS and CMS in mini-open TightRope group were better than that in hook plate group at 2 weeks after surgery (VAS: 2.19±0.92 vs. 3.30±1.51, p = 0.002 and CMS 69.80±5.61 vs. 57.53±9.24, p <0.001) and 3 month after surgery (VAS: 1.19±0.48 vs. 3.07±1.36, p <0.001 and CMS 89.30±4.47 vs. 83.20±12.11, p = 0.205). There was no statistically significant difference between two groups at 12 months follow-up including VAS, CMS, the CC distance, ΔCE and the degree of dynamic horizontal translation. There were 2 complications in the hook plate group including 1cut out and 1 superficial wound infection. Conclusion: The mini-open tightrope has better function and relieves pain in the early postoperative period compared to hook plate, and at the last follow up two groups have similar clinical and radiological outcomes. Mini-open TightRope fixation is a good option for the treatment of acute Rockwood types ⅢB AC joint dislocation.